Fluid-Structure Interaction Based Algorithms for IOP and Corneal Material Behavior - Maklad, Osama; Eliasy, Ashkan; Chen, Kai-Jung; Wang, JunJie; Abass, Ahmed; Lopes, Bernardo Teixeira; Theofilis, Vassilis; Elsheikh, Ahmed (Frontiers in Bioengineering and Biotechnology, 2020)
Purpose: This paper presents and clinically validates two algorithms for estimating intraocular pressure (IOP) and corneal material behaviour using numerical models that consider the fluid-structure interaction between the cornea and the air-puff used in non-contact tonometry. Methods: A novel multi-physics fluid-structure interaction model of the air-puff test was employed in a parametric numerical study simulating human eyes under air-puff pressure with a wide range of central corneal thickness (CCT=445 to 645 μm), curvature (R=7.4 to 8.4 mm), material stiffness and IOP (10 to 25 mmHg). Models were internally loaded with IOP using a fluid cavity, then externally with air-puff loading simulated using a turbulent computational fluid dynamics model. Corneal dynamic response parameters were extracted and used in development of two algorithms for IOP and corneal material behaviour; fIOP and fSSI, respectively. The two algorithms were validated against clinical corneal dynamic response parameters for 476 healthy participants. The predictions of IOP and corneal material behaviour were tested on how they varied with CCT, R and age. Results: The present study produced a biomechanically corrected estimation of intraocular pressure (fIOP) and a corneal material stiffness parameter or Stress-Strain Index (fSSI), both of which showed no significant correlation with R (p> 0.05) and CCT (P> 0.05). Further, fIOP had no significant correlation with age (p> 0.05), while fSSI was significantly correlated with age (p= 0.001), which was found earlier to be strongly correlated with material stiffness. Conclusion: The present study introduced two novel algorithms for estimating IOP and biomechanical material behaviour of healthy corneas in-vivo. Consideration of the fluid structure interaction between the cornea and the air puff of non-contact tonometry in developing these algorithms led to improvements in performance compared with bIOP and SSI.